2022
DOI: 10.1093/ajh/hpac079
|View full text |Cite
|
Sign up to set email alerts
|

Primary Aldosteronism: State-of-the-Art Review

Abstract: We are witnessing a revolution in our understanding of primary aldosteronism. In the past two decades, we have learned that primary aldosteronism is a highly prevalent syndrome that is largely attributable to pathogenic somatic mutations, that contributes to cardiovascular, metabolic, and kidney disease, and that when recognized, can be adequately treated with widely available mineralocorticoid receptor antagonists and/or surgical adrenalectomy. Unfortunately, primary aldosteronism is rarely diagnosed, or adeq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 308 publications
0
55
0
8
Order By: Relevance
“…On the other hand, it proved to be informative and may be valid in many cases. A shift toward more pragmatic testing for PA should be considered in light of the poor adherence to screening recommendations [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, it proved to be informative and may be valid in many cases. A shift toward more pragmatic testing for PA should be considered in light of the poor adherence to screening recommendations [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the deleterious effects of overt PA are widely appreciated, AAS is currently not an established disorder; mild PA forms remain largely unrecognized [ 7 ]. Our study demonstrates a relatively high prevalence of (possible) autonomous aldosterone excess among patients with adrenocortical adenoma/hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…
Primary aldosteronism (PA) is one of the most prevalent causes of endocrine hypertension [1][2][3]. A recent metaanalysis on the prevalence of PA showed that 4.3% of hypertensive patients in a primary care setting and 9.0% of referred patients had confirmed PA.
…”
mentioning
confidence: 99%